The fifth monarchy men - Capp, B; Capp, Bernard (1970)
﻿ Few predictions can have been less accurate than the claim by the anonymous author of London's Glory (1661) that the Fifth Monarchists would prove a 'never to be forgotten sect'. After brief literary glory as the subjects of Abraham Cowley's play Cutter of Coleman Street (1663), they languished in obscurity until revivified by Sir Walter Scott in 1822 in hia novel Peveril of the Peak. Since they have no modern descendants, the Fifth Monarchists have not received the close study by denominational historians which the Quakers, for example, have enjoyed. The Fifth Monarchists' call for violent revolution has led baptist and Congregationaiist historians to miniinize or ignore the close associations which these denominations had with the movement. The Fifth Monarchists showed few of the egalitarian tendencies of the Levellers and Diggers which have attracted so many modern Historians. In the present century the Fifth Monarchists have been the subjects of only two brief monographs. In 1911 Miss Louise Brown published her work, The Political Activities of the Baptists and Fifth Monarchy Men in England during the Interregnum, a careful and accurate survey of this aspect which, however, left untouched the broader issues of the nature of the movement, and the causes of its rise and decline. P.G.Rogers attempted a broader examination in the Fifth Monarchy Men (1966), but the brevity of this work and the inadequate research on which it was based made the results far from satisfactory. Four main aspects of the Fifth Monarchist movement have been studied, and these are indicated in the title of the thesis. These are, firstly, the circumstances which explain the origins and spread of millenarian ideas in general during this period, and of Fifth Monarchist doctrines in particular, and, secondly, the social composition of the movement. Thirdly, an attempt has been made to establish what political, social, economic and religious structures were envisaged by the Fifth Monarchists, and to explain why specific proposals were made. Lastly, an examination has been made of the later history of the movement, and the subsequent careers of its members. Chapters 1-3 sketch briefly the intellectual climate of the period, and then set the Fifth Monarchists in the context of the general European politico-religious situation following the Reformation. The unprecedented division of Western Europe was seen by many early Protestants as a cataclysmic event, explicable only in terras of the fulfilment of the prophecies of the end of the world. Subsequent political developments, such as the french and Dutch Wars of Religion and the Thirty Years' War, were fitted into the prophetic scheues of Daniel and Revelation. The standard interpretation of the prophecies had to be modified only slightly to guarantee the triumph of the godly (Protestants) before rather than after the end of the world. As early as the 1530s there was an attempt at Münster to set up a New Jerusalem, though the revolutionary political and social doctrines associated with this episode served to discredit millenarianism for many years. But in the early part of the seventeenth century, when the Protestant cause was again in danger of extinction, millenarianism flourished once more. In England, the government was sufficiently strong to prevent another Münster, but a series of self-proclaimed propnets and messiahs, a number of millenarian Puritan ministers and the writings of the academics Mede and Brightman all testified to interest in millenarian ideas. There was also a popular and related concept of England as a chosen nation, entrusted with the execution of God's cosmic plans. When the civil war broke out in 1642, it was rapidly placed by Puritan preachers in a millenarian framework, and accepted in this way by many in the army and in Parliament. A study of the writings of clergy supporting Parliament in the period 1640-53 suggests that about 70% of them believed that a last age of unparallelled glory was about to dawn. But millenarianism was a very flexible concept, and many who looked forward to a time of spiritual perfection abandoned a doctrine which many in the army and the sects equated with social revolution. The execution of King Charles, making way for King Jesus, intensified millenarian excitement, but the Rump did nothing to answer these hopes. The emergence of the Fifth Monarchist movement was a response to the apparent apostacy of all in authority from the millenarian cause. Fifth Monarchists claimed the right of the individual citizen, as saint, to throw down ungodly governments because they had despaired of the magistrates or any in official position doing so. They were an opposition movement, and always remained such except briefly during the Barebones Parliament of 1653. The composition of the Fifth Monarchist movement (chapter 4) reflects the importance of the New Model Army in its origin. Fifth Monarchism was a largely urban movement, and many of the towns where it flourished were garrison towns or naval establishments. Many of the saints had served in the army, as officers, soldiers, or chaplains. There are no Fifth Monarchist records comparable to the Quaker lists of births, marriages and deaths, but an analysis of the two hundred and thirty Fifth Monarchists whose occupations can be establisned gives some indication of their social composition. There was a small but important group of ministers and high-ranking army officers of relatively high social origin. Of the remainder, a large proportion, about 30%, were engaged in the cloth and leather industry and trade. Wone of them was a large-scale merchant or producer. The movement attracted only small masters, journeymen, apprentices and labourers. Grace was more important than birth, and there was no discrimination against those who were economically unfree. Servants and labourers could play an important role, and women were also prominent. A considerable amount of biographical information has been accumulated during the course of this study, and this has been summarized in the Biographical Appendix. The careers of some, such as Feake and William Medley, have been traced for thirty years after the last date when they were previously known. The Fifth Monarchists were a very loosely-organized body, and never formulated a common programme. But their main objectives can be established, and these are discussed in chapters 6-8. The evidence is drawn from the numerous manifestoes, declarations, sermons and biblical expositions published in the 1650s, and from the State Papers. The limited data from the Restoration period suggest that these objectives remained constant. The Fifth Monarchists demanded the destruction of the privileged orders, the national ministry, the lawyers, the great merchants, and the ungodly magistrates and nobility. In their place, they sought to establish a theocracy, an oligarchy of the 'visible saints', and to establish a new social structure in which godliness not birth would be the criterion of superiority. They called for a cheap and decentralized legal system using the Mosaic Code, and for the relief of the poor and of debtors. The principle of private property was accepted, but there were demands that the lands of the ungodly should be confiscated and re-distributed. The saints sought the encouragement of domestic production by a policy of protection and by a trade war against the Dutch, despite the fact that the latter were a Protestant nation. Beggars, debtors and thieves were all to be used as a pool of cheap labour for domestic industry. Despite the attacks on merchants, this programme cannot be classified simply as anti-capitalist. Its diversity is explained partly by the difference between the aspirations of the ministers and few gentry and those of the artisans. Yet even those who rebelled with Venner in 1661 called for protection and the utilization of beggars and thieves as cheap labour. Small masters saw the material advantages of such policies, even if they were 'capitalist' in tone. At the lowest social levels, the appeal of Fifth rtonarchism lay probably in the generalized vision of health and wealth and the prospects of revenue on all those who enjoyed social superiority. The Mosaic lows may have attracted the saints because their provisions ior thieves and debtors combined humanitarianism with the prospect of profit, but their introduction had in fact been urged by a long series of Protestant and Puritan writers. The demand reflected a and eneral Protestant interest in Jewish affairs. The concepts of the 'elect', the 'elect nation' and the 'second covenant', and the emphasis on the Bible directed interest towards the first chosen people, the 'people of the Book' and the first covenant. Many Fifth Monarchists and others looked for the conversion and return of the Jews, the adoption of the Mosaic Laws, and of the Seventh Day Sabbath, and one group adopted all the Jewish rites and proposed to rebuild the Temple. Chapter 9 examines the later history of the movement. The return of censorship ended the flow of Fifth Monarchist pamphlets, and the State Papers are the main source after 1660. Quarter-sessions records and visitation returns yielded a little information, but local officials for the most part failed to distinguish between the idiosyncrasies of the various sects. After tha Restoration, the movement gradually split into two parts. One of them became progressively more moderate, and was eventually absorbed into the Baptist and Congregationalist movements, which still retained pronounced millenarian tendencies. There is no evidence of a mass influx into Quakerism, as has sometimes been suggested. Relations between the Fifth Monarchists and Quakers were always very hostile; Quaker doctrines were highly offensive to the literalist and mostly predestinarian beliefs of the Fifth Monarchists. The second section turned towards violence, and participated in all the republican plots of the period, including the activities of Colonel Blood. In the 1670s they became involved with the Exclusionists. The Fifth Monarchist cause finally perished, with the Good Old Cause as a whole, at Sedgemoor in 1685. In the conclusion (chapter 10) there is a brief survey of the development of millenarianism on the continent after Münster. A final summary follows.